Serial diffusion-weighted MRI and SPECT findings in a Creutzfeldt–Jakob disease patient with V180I mutation - Kono, Syoichiro; Manabe, Yasuhiro; Fujii, Daiki; Sakai, Yasuko; Narai, Hisashi; Omori, Nobuhiko; Kitamoto, Tetsuyuki; Abe, Koji (Journal of the neurological sciences, 2011)
We report serial changes of diffusion-weighted imaging (DWI) and single photon emission computed tomography (SPECT) in a patient with Creutzfeldt–Jakob disease with V180I mutation (CJD180). DWI abnormalities in our patient were more predominantly observed in the left cerebral cortex than left basal ganglia. Hemilateral abnormalities progressed over 5 months to involve the contralateral side with increasing DWI signals. At 6 months, SPECT showed hypoperfusion in the left parietal and frontal lobes and the hypoperfusion region spread to the bilateral basal ganglia, right parietal and frontal lobes. SPECT imaging revealed marked cerebral blood flow reduction, predominantly in the cerebral cortex corresponding to brain areas with high-intensity DWI signals. During the follow-up period of CJD180, DWI was more sensitive than conventional FLAIR and T2-weighted images (T2WI) to detect and monitor the progression of abnormal hyperintense lesions. We suggest that serial DWI and SPECT findings are useful for not only early diagnosis of CJD but also for monitoring disease progression.